The Impact of Job Satisfaction on Teachers’ Retention Intention in Rural Primary and Secondary Schools in Anyang City, Henan Province, China—The Moderating Role of Family Support - Yin, Nanfang; Wang, Hsuan-Po; Chen, Lingling (Journal of China-ASEAN Studies, 2023)
The purpose of this study is to investigate the impact of job satisfaction among rural primary and secondary school teachers in different age groups in Anyang City, Henan Province, China, on their intention to stay in their current positions, with family support as a moderating variable. A questionnaire survey was conducted using convenience sampling, involving 380 rural primary and secondary school teachers in Anyang City, Henan Province. The results of the study indicate: 1. Job satisfaction among rural primary and secondary school teachers in Anyang City, Henan Province, has a significant positive impact on their intention to stay in their current positions. 2. Family support among rural primary and secondary school teachers in Anyang City, Henan Province, moderates the relationship between job satisfaction and intention to stay.